2020
DOI: 10.3389/fphar.2020.00914
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Coupling Between Drug Binding and the Aromatic Cassette in the Pore Domain of the hERG1 Channel: Implications for a State-Dependent Blockade

Abstract: translocation of ivabradine into the central cavity. M651T mutation appears to disrupt this entry pathway by altering the molecular conformation of F656.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…S8B and C ) Hence up to two sotalol molecules were able to bind to the hERG pore, in agreement with our electrophysiological data (as described below). Sotalol flooding MD simulations demonstrated that d- and l-sotalol are likely to enter the hERG channel pore through the aqueous intracellular gate and did not reveal any drug entry through lipid facing fenestrations as in the case of Na V channels [ 91 94 ] and also suggested for some hERG binding drugs such as ivabradine [ 95 , 96 ]. Thus, sotalol hERG pore binding pathways closely resemble those for dofetilide [ 61 , 63 , 95 , 96 ], which also has methanesulfonanilide moieties and fairly similar polarity [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…S8B and C ) Hence up to two sotalol molecules were able to bind to the hERG pore, in agreement with our electrophysiological data (as described below). Sotalol flooding MD simulations demonstrated that d- and l-sotalol are likely to enter the hERG channel pore through the aqueous intracellular gate and did not reveal any drug entry through lipid facing fenestrations as in the case of Na V channels [ 91 94 ] and also suggested for some hERG binding drugs such as ivabradine [ 95 , 96 ]. Thus, sotalol hERG pore binding pathways closely resemble those for dofetilide [ 61 , 63 , 95 , 96 ], which also has methanesulfonanilide moieties and fairly similar polarity [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several recent publications have commented on the apparent difficulties in docking or simulations of the binding of diverse ligands known to bind to the very constricted and hydrophobic environment of the IC cavity found in the cryo-EM structure. 28,29,33 The receptor flexibility plays an apparent role in the high-affinity binding to the intracavitary site and SILCS-MC has the potential to map the site directly in the presence of explicit lipid bilayer and solvent molecules. SILCS-Hotspots for the hERG1 identified favorable binding spots for the ring based fragments, which are termed as "hotspots"; 145 hotspots were identified with average LGFE scores for the fragments occupying each hotspot ranging from −2.3 to −4 kcal/mol in the PD, VSD, and the intracellular terminal of the hERG1 channel (Figure 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A similar finding of two distinct pockets is recently published for dofetilide. 33 S1 corresponds to the deeper classic drug-binding pocket in the immediate vicinity of F656 or Y652. These hotspots are mapping the primary binding pocket in the IC reported in many previous studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond ligand-based methods, SBDD approaches may yield an understanding of the underlying atomistic interactions and binding orientations contributing to hERG binding and blockade. Accordingly, a number of research groups have applied structure-based simulation and docking approaches in modeling ligand interactions with hERG channels, revealing the benefits the SBDD approach can offer when compared to ligand-based techniques [48][49][50][51][52][53][54][55][56][57]. A contribution in this direction was recently reported by Mangiatordi and coworkers for a large number of compounds, where they showed the utility of docking scores and their integration with protein-ligand interaction fingerprints [58].…”
Section: Introductionmentioning
confidence: 99%